Physical activity in adolescents: analysis of the social influence of parents and friends - Luanna Alexandra Cheng; Gerfeson Mendonça; José Cazuza de Farias Júnior (Elsevier, 2014)
Objective: to analyze the association between physical activity and social support from parents and friends on the physical activity level among adolescents. Methods: data from 2,361 adolescents (56.6% females; mean age 16.4; SD = 1.2), from public and private high schools were analyzed. The physical activity level of the adolescents, parents, and friends were measured through a questionnaire. Parents' and friends' support and self-efficacy were measured using two previously tested scales. Data analysis was performed using the structural equation modeling in IBM® SPSS® Amos™ 20.0. Results: physical activity of friends was directly associated with physical activity level of adolescents. Physical activity of the father was associated with that of their sons, and the physical activity of mother was associated with that of their daughters. An indirect association was identified between the physical activity of parents and friends with physical activity level of the adolescents, mediated by social support. Social support was directly associated with physical activity in adolescents of both genders and indirectly mediated by self-efficacy. Conclusions: parents and friends have a social influence on adolescents' level of physical activity through the mechanism of behavior modeling or through social support, mediated by self-efficacy. Resumo: Objetivo: analisar a associação da prática de atividade física e do apoio social dos pais e dos amigos com o nível de atividade física dos adolescentes. Métodos: foram analisados dados de 2,361 adolescentes (56,6% do sexo feminino, média de idade = 16,4; dp = 1,2) do ensino médio de escolas públicas e privadas. A atividade física dos adolescentes, dos pais e dos amigos foi mensurada por questionário. O apoio social dos pais e dos amigos e a autoeficácia foram mensurados por duas escalas previamente testadas. A modelagem por equações estruturais foi utilizada para análise dos dados, recorrendo-se ao programa AMOS 20.0. Resultados: a prática de atividade física dos amigos se associou diretamente ao nível de atividade física dos adolescentes, enquanto a prática do pai se associou diretamente com a do filho e a da mãe com a da filha. Também foi identificada uma relação indireta entre a prática de atividade física dos pais e dos amigos e o nível de atividade física dos adolescentes, sendo parcialmente mediada pelo apoio social desses dois grupos. O apoio social dos pais e dos amigos se associou diretamente à atividade física do adolescente, e foi mediado, indiretamente pela percepção de autoeficácia. Conclusões: pais e amigos exercem influência social sobre a prática de atividade física dos adolescentes por meio da modelação do comportamento e do fornecimento de apoio social. Keywords: Motor activity, Adolescents, Parents, Friends, Social support, Palavras-chave: Atividade motora, Adolescentes, Pais, Amigos, Apoio social